Assessment of Vitamin D among University Students during Covid-19 Period (Medical Forum Monthly, 2023)
Objective: Pakistan has one of the highest rates of vitamin D deficiency but the research on vitamin D related knowledge, attitudes, and habits among Pakistan's healthy youth during COVID-19 period has not been done sufficiently. This type of study was necessary to determine the vitamin D levels, dietary routines and prevalence of vitamin D deficiency among university students of Hyderabad.Study Design: Cross Sectional studyPlace and Duration of Study: This study was conducted at the University of Sindh over the period of 5 months from September 2021 to December 2021.Materials and Methods: In the university students during the COVID-19 Pandemic a Pre structured questionnaire was distributed with questions regarding the daily routine and diet. A total of 145 students took part in the survey. The students were divided into three age groups: 18-20, 21-23, and 24-26 years old. Out of the 145 individuals, 82 (57%) were female and the remaining 63 (43.4%) were male.Results: 90% students were unaware of Vitamin D and more than 50% were not taking Vitamin D supplement in any form. Only 5.7% of students were taking Vitamin D pills, whereas 8.1% consumed milk and vitamin D-rich foods. 15.5% of people used sunscreen to their faces on a regular basis, whereas 10% used it on their hands. Similarly, their sun exposure and outdoor activities were severely limited.Conclusion: The University students were found lacking the vitamin D related knowledge, positive attitude and proper practice. Also due to the pandemic amid lockdown situation, many students were unable to get sun exposure source of Vitamin D on daily basis. Our current research also concluded that there was a dire need of conducting awareness campaigns and motivational programs at university level during pandemic situations like COVID-19.